Floppy's phonics sounds and letters :planning, assessment and resources - Hepplewhite, Roderick; Brychta, Alex Hunt, Roderick (Oxford University Press Oxford, 2011)
The Planning, Assessment and Resources Book offers guidance and resources to help manage your teaching and assessment.